(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
The lack of sufficient knowledge about climate changes and the impact on agricultural production is an impediment to long term sustainable agriculture in most developing countries, including Bangladesh. This paper presents the results of an investigation to determine perception of farmers about changes in climate in Bangladesh. The study finds the determinants of farmers perception on climate variability in different specifications of household characteristics. The sample was adult farmers with at least 20 years of farming experience in the area. Data was collected on perceptions about temperature changes and variability in precipitation over a 20 year period. The results indicated that more than 80% of farmers believe that temperature in the district had become warmer and over 90% were of the opinion that rainfall timing had changed, resulting in increased frequency of drought. Res. Agric., Livest. Fish.3(1): 27-35, April 2016